1999
DOI: 10.1007/s002469900510
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Presentation of Congenital Long QT Syndrome

Abstract: Thirty-two-week prenatal ultrasound revealed a fetal heart rate of 100 bpm with decreased variability on the heart rate tracing. Echocardiogram documented normal anatomy and sinus bradycardia. Newborn electrocardiogram revealed sinus rhythm at 100 bpm with a QTc of 0.657. Follow-up electrocardiogram revealed a QTc interval of 0.568, 2:1 atrioventricular block with a ventricular rate of 60 bpm, and ventricular ectopy. The infant received a pacemaker and beta-blocker therapy. Long QT syndrome should be in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Wandering pacemaker was another cause of this type of fetal bradycardia. Although we did not experience this in our study, a recent report showed that some neonates with long QT syndrome had had bradycardia with 1 : 1 atrioventricular conduction during the prenatal period15, 16.…”
Section: Discussionmentioning
confidence: 67%
“…Wandering pacemaker was another cause of this type of fetal bradycardia. Although we did not experience this in our study, a recent report showed that some neonates with long QT syndrome had had bradycardia with 1 : 1 atrioventricular conduction during the prenatal period15, 16.…”
Section: Discussionmentioning
confidence: 67%
“…In particular, attention should be paid to fetuses with a slightly reduced FHR of 110–120 bpm as well as fetuses with bradycardia <110 bpm, tachyarrhythmias or clinical signs of heart failure, such as pleural effusion and hydrops. As shown in cases 6, 9, 10 and 11 in table 1, some fetuses with LQTS exhibit a reduced heart rate variability [6,9,10,11]. Fetal magnetocardiography is able to detect the prolongation of the QT interval [9,11,14,20] as well as subtle changes in the short-term heart rate variability [41], thereby facilitating the prenatal diagnosis of LQTS [9,11,14,20].…”
Section: Discussionmentioning
confidence: 99%
“…The search terms ‘long QT syndrome’, ‘fetal arrhythmia’ and ‘congenital heart disease’ were used. The 30 reports were classified into three categories according to content: 20 reports [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21] describing 21 patients with LQTS documented abnormal cardiac findings found in utero (table 1); 5 reports [23,24,25,26,27] described series of LQTS patients and included prenatal cardiac findings for some of the fetuses (table 2), and 5 reports [28,29,30,31,32] described series of fetuses, some of whom were subsequently diagnosed as having LQTS, for whom echocardiography examinations had been performed because of abnormal cardiac findings detected incidentally during antenatal care (table 3). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these studies have involved small numbers of cases of SCD, and have not been replicated [72]. A number of reports indicate that that monogenic arrhythmia syndromes can present as the Sudden Infant Death Syndrome (SIDS) [7375]. …”
Section: Current Status Of Scd Genetics and Pharmacogeneticsmentioning
confidence: 99%